Pyridoxol metabolism in vitamin B6-responsive convulsions of early infancy. Issue 10 (October 1978) - Heeley, A; Pugh, R J; Clayton, B E; Shepherd, J; Wilson, J
Abstract : As there is uncertainty about the nature of the metabolic defect in vitamin B6-responsive convulsion, certain aspects of pyridoxol metabolism were studied in 3 patients who were believed on clinical grounds to have the condition. The findings were compared with those in healthy children and adults, and in children with mental handicap. The magnitude of the initial rise and the subsequent fall in plasma pyridoxal phosphate (PALP) concentrations after a load of pyridoxol suggested that the vitamin B6-responsive patients were able to synthesise PALP normally but were unable to maintain the prolonged high levels normally found in plasma. The urinary excretion of 4-pyridoxic acid was within normal limits, but the excretion of pyridoxol after the load was raised. It is suggested that there may be an instability of the PALP-albumin complex in this condition. Some of the biochemical features were also observed in an infant presenting with convulsions soon after birth but without evidence of clinical B6-dependency.